2022
DOI: 10.1038/s42255-022-00567-z
|View full text |Cite
|
Sign up to set email alerts
|

A glucose-like metabolite deficient in diabetes inhibits cellular entry of SARS-CoV-2

Abstract: The severity and mortality of COVID-19 are associated with pre-existing medical comorbidities such as diabetes mellitus. However, the underlying causes for increased susceptibility to viral infection in patients with diabetes is not fully understood. Here we identify several small-molecule metabolites from human blood with effective antiviral activity against SARS-CoV-2, one of which, 1,5-anhydro-d-glucitol (1,5-AG), is associated with diabetes mellitus. The serum 1,5-AG level is significantly lower in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…Together with the H&E staining (Figure 3b) which showed well-organized structures and high similarities compared with nasal biopsy reported in the literatures (20)(21)(22), the nasal organoids were confirmed as successfully constructed. The 2-D airway organoids were then applied in the infection model as a testing platform for the neutralization effect of the antibodies.…”
Section: -D Airway Organoid Construction and Sars-cov-2 Infectionsupporting
confidence: 69%
“…Together with the H&E staining (Figure 3b) which showed well-organized structures and high similarities compared with nasal biopsy reported in the literatures (20)(21)(22), the nasal organoids were confirmed as successfully constructed. The 2-D airway organoids were then applied in the infection model as a testing platform for the neutralization effect of the antibodies.…”
Section: -D Airway Organoid Construction and Sars-cov-2 Infectionsupporting
confidence: 69%
“…28 Nevertheless, their antiviral activity against other sublineages, such as BA.4 and BA.5, still needs further assessment. Besides, many preclinical antiviral agents, such as 1,5-anhydro-d-glucitol (1,5-AG), 70 and the pan-CoV fusion inhibitors, such as EK1 and EK1C4, 71 targeting the conserved site in S2 protein, also have good potential to broadly inhibit infection by SARS-CoV-2 variants and Omicron sublineages. For example, EK1 and EK1C4 can potently inhibit fusion mediated by S protein of WT SARS-CoV-2, Delta VOC, and Omicron BA.1.…”
Section: Origin Of the Omicron Variantmentioning
confidence: 99%
“…Similar results were obtained in the present study during the Omicron variant wave. Glucose-like metabolite deficiency may facilitate viral entry and replication, as described previously [ 21 ]. Another mechanism is that the production of neutralizing antibodies is reduced in diabetes [ 18 , 26 ].…”
Section: Discussionmentioning
confidence: 88%
“…The in vitro experiment confirmed that increased glucose concentration decreases the viability of A549 cells and induces ACE2 overexpression [ 20 ]. In addition, viral loads are high, and respiratory tissue damage is severe in the diabetic mice model [ 21 ].…”
Section: Introductionmentioning
confidence: 99%